Archbishop Mikael Sallantyan’s letter to Nerses Ashtaraketsi - Hakobyan, Narek (History and Culture, 2023)
The sources of the history of relations between the Armenian Apostolic Church and Armenian Protestant are diverse in their type and content. Among the primary sources, the memoirs of the first evangelical missionaries William Goodell (Forty years in the Turkish Empire), Eli Smith (Missionary Researches in Armenia) and others, Mission Herald magazine take an important place. Along with the above-mentioned primary sources, the documents kept in the archive fund of Alexander Yeritsyan of the Mashtotsyan Matenadaran are of great importance from the scientific point of view. Among many documents, we have prepared a remarkable document for publication: the letter of Archbishop Michael Sallantian to Nerses Ashtaraketsi. In the letter, the author addresses a number of important issues, in particular: how the missionaries worked, how the evangelical communities expanded, what kind of education the apostolic and evangelical schools offered. The letter also addresses the nviraks (priestes to traveled from region to region and gathered donations for the Church) of the Armenian Apostolic Church and the activities of the Armenian Catholics.